Downregulation of miR-181b-5p Inhibits the Viability, Migration, and Glycolysis of Gallbladder Cancer by Upregulating PDHX Under Hypoxia - Qin, Yiyu; Zheng, Yongliang; Huang, Cheng; Li, Yuanyuan; Gu, Min; Wu, Qin (Frontiers in Oncology, 2021)
Background: Gallbladder cancer (GBC) is a malignant cancer with poor prognosis. Evidences have shown that miRNAs are closely related to the occurrence of GBC; thus, we aimed to explore miRNAs which plays an important role in the occurrence and development of GBC. Methods: RNA sequencing analysis was performed to investigate the differentially expressed miRNAs between five non-neoplastic gallbladder tissues (normal tissues) and five gallbladder tumor tissues (tumor tissues). RT-qPCR was performed to detect the level of miR-181b-5p in cells and CCK-8 was performed to detect cell viability. Then, Glucose Assay Kit or Lactic Acid assay kit was performed to detect the level of glucose consumption or lactate production. Next, transwell and wound healing assays were used to assess cell migration. In addition, dual-luciferase reporter assay was used to verify the relationship between miR-181b-5p and PDHX. At last, western blotting was performed to determine the protein level of PDHX. Results: RNA sequencing analysis suggested miR-181b-5p was significantly upregulated in GBC tumor tissue. KEGG analysis for the protein targets of miR-181b-5p indicating a close relationship existed between miR-181b-5p and glycolysis. In addition, the level of miR-181b-5p was notably increased in GBC-SD or G415 cells, compared with HIBEpiC cells. GBC cell viability was significantly decreased under hypoxia, and these decreases were exacerbated by miR-181b-5p antagomir. Moreover, glucose consumption or lactate production of GBC cells was significantly upregulated under hypoxia, while these increases were completely revered by miR-181b-5p antagomir. Further investigation revealed that PDHX was a direct target of miR-181b-5p. Conclusion: In this study, downregulation of miR-181b-5p inhibits the viability, migration and glycolysis of GBC by upregulating PDHX under hypoxia. This finding suggested that miR-181b-5p might be considered as a novel therapeutic target for the treatment of GBC.